The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1094/phyto-73-282
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Atmospheres on Postharvest Decay and Quality of Fresh Strawberries

Abstract: Effects of different atmospheres, ie, air + ethylene (C 2 H 4) at 20 11/ L; air + added to either air or CA, resulted in more decay development than in other 15% CO 2 ; air + 10% carbon monoxide (CO); a controlled atmosphere (CA) atmospheres, indicating that C 2 H 4 might enhance disease development or of 2.3%02+5%CO 2 ; CA +C 2 H 4 (20,4l/ L); and CA + 10% CO in addition fungal growth. Off-flavors were detected after treatment with air + 15% to control (air), on the postharvest decay of strawberry fruits caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
81
1
2

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 2 publications
10
81
1
2
Order By: Relevance
“…In this study the presence of B. cinerea was only observed in the packages under air at the end of storage (85-100%), as seen in figure 2. These results are in agreement with the observations of El-Kazzaz et al and Sommer et al, who reported that exposure to CO 2 levels between 5 and 20%, had some fungi static effects on strawberry pathogens [49,50]. Hence any of the packages except packages under air could prove suitable for inhibiting Botrytis growth for 3week at 4°C.…”
Section: Fungal Decaysupporting
confidence: 92%
See 2 more Smart Citations
“…In this study the presence of B. cinerea was only observed in the packages under air at the end of storage (85-100%), as seen in figure 2. These results are in agreement with the observations of El-Kazzaz et al and Sommer et al, who reported that exposure to CO 2 levels between 5 and 20%, had some fungi static effects on strawberry pathogens [49,50]. Hence any of the packages except packages under air could prove suitable for inhibiting Botrytis growth for 3week at 4°C.…”
Section: Fungal Decaysupporting
confidence: 92%
“…Gains in firmness were greater (P<0.05) for strawberries packed under MAP owing to the increasing CO 2 concentration in the package headspace. Thus after 7 days at 4°C the firmness of strawberries packed under MA1 and MA2 that were dripped with CaCl 2 increased by 2.55and 2.52 N cm-2 respectively, which is in accordance with the results of El-Kazzar et al for cultivated strawberries [49]. Although it is known that the mechanical properties of fruits depend on cell wall strength, cell-to-cell adhesion, cell packing and the internal pressure or turgor of cells [54], the mechanism responsible for CO 2 -induced firming of strawberry tissue is still unknown.…”
Section: Firmnesssupporting
confidence: 90%
See 1 more Smart Citation
“…Depending on the plantpathogen interaction, treatment with ET may enhance resistance (Esquerré-Tugayé et al, 1979;El-Kazzaz et al, 1983b;Marte et al, 1993), induce susceptibility, or have no effect (El-Kazzaz et al, 1983a;Brown and Lee, 1993;Thomma et al, 1999). Our data indicate a crosstalk between PA and ET in modulating responses to B. cinerea.…”
Section: Discussionmentioning
confidence: 81%
“…이러한 품질저하 요인을 방지하고 선도를 유지하 기 위해서는 수확 후 관리가 필요하다 (Eum and Lee, 2007;Wills and Kim, 1995). 딸기의 선도를 유지하기 위한 방안으 로는 수확 즉시 예냉하는 방법 (Salunkhe and Desai, 1984), 부패와 호흡을 억제하고 경도를 유지시키는 고농도 CO 2 처 리(El- Kazzaz et al, 1983;Ke et al, 1991), 잿빛곰팡이병 발생억제를 위한 UV-C 처리 (Marquenie et al, 2003) 감모율은 'Goha'에서 저장 15일에 대조구가 2.5%로 가장 많았으며, CO 2 + ClO 2 처리구가 1.6%로 가장 적게 나타났 다 (Fig. 2).…”
unclassified